Salvage Treatment of Mucormycosis Post-Liver Transplant With Posaconazole During Sirolimus Maintenance Immunosuppression. (April 2017) - Deyo, Jennifer C.; Nicolsen, Nicole; Lachiewicz, Anne; Kozlowski, Tomasz
We describe the first successful case of posaconazole salvage therapy for mucormycosis with concomitant sirolimus (SRL) maintenance immunosuppression following liver transplantation, despite black box drug interaction following intolerance to first-line tacrolimus and amphotericin due to nephrotoxicity and neurotoxicity. This case describes a 55-year-old female who developed rhinocerebral mucormycosis 108 days after liver transplantation. After 3 months of posaconazole therapy, the patient remains free of disease at 3 years posttransplant. This case report illustrates successful resolution of mucormycosis without SRL toxicity to resolve nephrotoxicity of long-term amphotericin on top of already nephrotoxic immunosuppression. With higher bioavailability of recently FDA-approved posaconazole delayed release tablets, this azole may be a therapeutic option for transplant patients who need to remain on CYP3A4-metabolized immunosuppressive agents.